2012
DOI: 10.1007/s11010-012-1426-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of diorganoyl diselenides and ditellurides: modulation by organic aryl or naphthyl moiety

Abstract: Diorganoyl dichalcogenide compouds can have antioxidant activity in different in vitro and in vivo models. Here, we have compared the potential antioxidant activity of 1-dinaphthyl diselenide (1-NapSe)(2), 2-dinaphthyl diselenide (2-NapSe)(2), 1-dinaphthyl distelluride (1-NapTe)(2), 2-dinaphthyl ditelluride (2-NapTe)(2) with their well-studied analogs diphenyl diselenide ((PhSe)(2)) and diphenyl telluride ((PhTe)(2)). (PhSe)(2), (PhTe)(2), and naphthalene analogs-inhibited Fe(II)-induced lipid peroxidation, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…This is in agreement with the promising results obtained on the antioxidant efficiency of organotellurides, which have paved the route for their use as drugs . In fact, their toxicity seems to be comparable to that of organoselenides, which have been studied for a few decades and represent the paradigmatic GPx mimics. High peroxidase efficiency has also been reported for a cyclodextrin‐derived tellurium compound …”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the promising results obtained on the antioxidant efficiency of organotellurides, which have paved the route for their use as drugs . In fact, their toxicity seems to be comparable to that of organoselenides, which have been studied for a few decades and represent the paradigmatic GPx mimics. High peroxidase efficiency has also been reported for a cyclodextrin‐derived tellurium compound …”
Section: Introductionmentioning
confidence: 99%
“…In addition, Te compounds have been investigated as chemopreventive agents and diphenylditelluride appears to have a very high capacity of inducing apoptotic cell death. 27,33 Importantly, the toxicity of organotellurides is found to be comparable to organoselenides and this paves the route to their possible use as drugs, in particular as antioxidant GPx mimics, although careful control is warmly recommended. 27,33 From a mechanistic point of view, small organoselenium compounds show some limitations and often their catalytic activity is relatively poor.…”
Section: Introductionmentioning
confidence: 99%
“…27,33 Importantly, the toxicity of organotellurides is found to be comparable to organoselenides and this paves the route to their possible use as drugs, in particular as antioxidant GPx mimics, although careful control is warmly recommended. 27,33 From a mechanistic point of view, small organoselenium compounds show some limitations and often their catalytic activity is relatively poor. 24 On the basis of the available experimental and computational studies this can be ascribed to (i) a competing undesired thiol exchange reaction which hampers the regeneration of the selenol, 34 due to the fact that nucleophilic attack at Se (reaction III, Scheme 1) is both thermodynamically and kinetically favored; 35,36 (ii) the nature of the thiol cosubstrate, which may have a dramatic effect on the catalytic activity of ebselen and its analogues; [37][38][39][40] (iii) the nonspecificity for the substrate which leads to undesirable reactions with Cys residues in different protein sites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that diphenyl diselenide 1 may interfere with the synthesis of heme-containing proteins via ALA-D inhibition [60]. Braga, Rocha, Nogueira and co-workers have been studying exten- sively the applications of diphenyl diselenide and its derivatives in biochemistry, pharmacology and toxicology, with a particular focus on the synthetic aspects [12,15,35,37,38,50,[53][54][55]. In presence of hydroperoxides and thiols, nucleophilic attack of sulfur at a selenium center occurs first, promoting Se-Se bond cleavage [143].…”
Section: Se Sementioning
confidence: 99%
“…Since few decades, much effort has been dedicated to the synthesis and reactivity properties of organochalcogenides as mimics of GPx for their potential anti-oxidant activity and possible use as drugs [12,13]. Organoselenides are undoubtedly the most studied, although also organotellurides have shown promising results in vitro as well as in vivo [12,[14][15][16]. From a biochemical point of view, the most remarkable differences between sulfur and selenium are the larger polarizability of Se and the lower pKa of SeH [11].…”
Section: Introductionmentioning
confidence: 99%